Association between weekday sleep, weekday-weekend sleep duration gap, and hypertension in American adolescents: a nationwide cross-sectional study - Luo, Yan; Li, Qingyuan; Feng, Tong; Duan, Ran; Chen, Yingyi (Frontiers in Psychiatry, 2024)
BackgroundThe increasing prevalence of primary hypertension among children and adolescents is a global health concern, with inadequate sleep duration identified as a significant risk factor. This study investigates the impact of weekday-weekend sleep duration gap (WWSDG) on hypertension among American adolescents.MethodsUsing data from the NHANES 2017-2020 cohort, we analyzed sleep patterns and hypertension prevalence among 430 adolescents. Sleep durations on weekdays and weekends were used to calculate WWSDG. Hypertension was defined according to the American Academy of Pediatrics guidelines.ResultsThe study found that among 430 American adolescents, shorter weekday sleep duration (less than 8 hours) was significantly associated with an increased risk of hypertension (OR: 1.092, 95% CI: 1.042–1.144), while extended weekend sleep did not show a protective effect. Additionally, longer total weekly sleep duration (over 10 hours) was linked to a reduced risk of hypertension, but the difference in sleep duration between weekdays and weekends was not significantly correlated with hypertension risk.ConclusionsThe study highlighted that insufficient weekday sleep duration significantly increases hypertension risk among adolescents. Contrary to popular belief, compensating for sleep deprivation through extended WWSDG did not mitigate this risk. Public health interventions should focus on promoting consistent and adequate sleep throughout the week for cardiovascular health benefits in adolescents. Further longitudinal research is necessary to explore causal relationships and the long-term effects of sleep variability on health outcomes.